Medición de materiales con radiación THz - Escobar Mejía, Andrés Felipe (2018)
This paper presents the experimental measurement of different materials when are irradiated by terahertz radiation (THz), applying THz spectroscopy techniques in the time domain. The radiation is emitted by a photoconductive antenna, excited by a femtosecond laser. The results are obtained when measuring the THz pulse transmitted through the materials when implementing a coherent and incoherent detection systems.